3. Uluslararasi Istanbul Bienali. - The Greater Istanbul Municipality Nejat F. Eczacibasi Art Museum, Istanbul; 3rd International Istanbul Biennial (Istanbul : Istanbul Foundation for Culture and Arts, 1992)
Erjautz, Manfred ; Hoek, Richard ; Wagnest, Matta ; Zobernig, Heimo ; Fabre, Jan ; Kostov, Lyuben ; Rouzhev, Georgi ; Solakov, Nedko ; Absalon ; Boltanski, Christian ; Othoniel, Jean-Michel ; Oudendijk, Sonja ; Sanders, Willem ; Semah, Joseph ; Likely, Seymour ; Collins, Hannah ; Hirst, Damien ; Aguilar, Sergi ; Alvarez Basso, Dario ; Badiola, Txomin ; Von Berner, Darya ; Quintanilla, Francisco L. ; Uslé, Juan ; Cohen Gan, Pinchas ; Ganor, Atsmon ; Kantor, Zvika ; Sack, Daniel ; Ziv, Neta ; Ariente, Stefano ; Bianchi, Domenico ; Fermariello, Sergio ; Garutti, Alberto ; Guerzoni, Franco ; Nunzio ; Bond, Eleanor ; Campbell, Colin ; Collins, Catherine ; Dempsey, Sawna ; Sterbak, Jana ; Tod, Joanna ; Yoon, Jin-me ; Baranowska, Zuzanna ; Kruk, Mariusz ; Smoczynski, Mikolaj ; subREAL ; Albert, Jurii ; Avvakumov, Jurii ; Shutov, Sergei ; Bogdalov, Farid ; Litichevskii, Georgi ; Filippov, Andrei ; Gutoff, Dmitri ; Kaminnik, Igor ; Fishkin, Vadim ; Scholokov, Andrei ; Kuprainov, Vladimir ; Leiderman, Jurii ; Ostritsov, Georgi ; Revolutionary Carrier ; Zvezdochetov, Konstantin ; Birsel, Selim ; Karamustafa, Gülsün ; Onur, Hakan ; Tenger, Hale ; Tolon, Canan
3rd International Istanbul Biennial, The Greater Istanbul Municipality Nejat F. Enzacibasi Art Museum, Istanbul, 17.10 - 30.11.1992
boek